2007
DOI: 10.1007/s11904-007-0029-2
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in internet-and cell phone-based HIV prevention and intervention programs

Abstract: As the reach of the Internet and cell phones increases, their use as health intervention and prevention tools has been increasingly researched. To identify recent advances in technology-based HIV prevention and intervention research, we conducted a literature search in the Spring of 2007. Only a handful of articles have been published in the last year describing evaluations of technology-based HIV programs. Nonetheless, many programs have recently been funded and are being developed or imminently evaluated. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
118
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(119 citation statements)
references
References 36 publications
1
118
0
Order By: Relevance
“…Perhaps, supportive sobriety and clean time text messages could be sent to homeless people working toward recovery; reminder text messages could be sent about fellowship meetings as well. Prevention and intervention programs delivered through mobile phones for human immunodeficiency virus, 34 tobacco use, 35,36 and medication adherence 37 have been developed and found to be feasible and effective in various populations. If tailored appropriately, these programs may work with homeless people as well and potentially increase access to much-needed services at a relatively low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, supportive sobriety and clean time text messages could be sent to homeless people working toward recovery; reminder text messages could be sent about fellowship meetings as well. Prevention and intervention programs delivered through mobile phones for human immunodeficiency virus, 34 tobacco use, 35,36 and medication adherence 37 have been developed and found to be feasible and effective in various populations. If tailored appropriately, these programs may work with homeless people as well and potentially increase access to much-needed services at a relatively low cost.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile health (mHealth) represents one such tool with capacity for reaching otherwise hidden populations. [30] MHealth possesses particular promise for YGBM given their preference for online sexual health support, [31][32][33] the pervasiveness of mobile technologies throughout Romania, [34][35][36] and the ability of mHealth technologies to bypass barriers to healthcare for marginalized populations by bringing prevention "to their pockets." [37] The current study was designed to test whether an mHealth HIV-prevention intervention would be feasible, acceptable, and efficacious in supporting the HIV prevention and related health needs of YGBM in Romania.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of realtime interventions appears to be enhanced when EMA are used to tailor content delivered within the EMI [13]. In domains other than alcohol use, real-time mobile phone interventions have shown success at improving health behaviour, including sexual health and risk behaviour [14,15], smoking cessation [16,17], weight management [18,19] and physical activity [20]. However, there is little literature describing investigations of the effects of real-time EMI for alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, both Riordan et al and Suffoletto et al undertook forms of EMA and interventions for alcohol consumption, but neither attempted screening or intervention during drinking events. While both studies used methods which are innovative within the alcohol field, neither attempted to intervene at the time that the targeted behaviour was actually occurring, as has proven effective in other health domains [14,15] Studies have shown that brief interventions delivered using web and mobile phone platforms can be effective for reducing alcohol consumption in young people. Mobile phones in particular offer opportunities to collect data and deliver interventions anywhere and anytime, due to their high usage and portability.…”
Section: Introductionmentioning
confidence: 99%